2021
DOI: 10.1101/2021.07.01.450676
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neutralization of Delta variant with sera of Covishield vaccinees and COVID-19 recovered vaccinated individuals

Abstract: The recent emergence of B.1.617 lineage has created grave public health problem in India. The lineage further mutated to generate sub-lineages B.1.617.1 (Kappa), B.1.617.2 (Delta), B.1.617.3. Apparently, the Delta variant has slowly dominated the other variants including B.1.617.1 (Kappa), B.1.617.2 (Delta), B.1.617.3. With this, World Health Organization has described this sub-lineage as variant of concern. The high transmissibility associated with Delta variant has led to second wave of pandemic in India whi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…The sera of the heterologous group was efficient in neutralizing VOCs; Alpha, Beta and Delta as we have previously reported with two doses of Covaxin and Covishield 16. 17,18 .…”
Section: Discussionsupporting
confidence: 56%
“…The sera of the heterologous group was efficient in neutralizing VOCs; Alpha, Beta and Delta as we have previously reported with two doses of Covaxin and Covishield 16. 17,18 .…”
Section: Discussionsupporting
confidence: 56%
“…The VE of two doses of Oxford-ChAdOx1-S against severe infection with the Delta variant in United Kingdom was 67% (Lopez Bernal et al, 2021). Indian studies indicated reduced neutralization capability of BBV152/Covaxin and AZD1222/Covishield vaccine against Delta variant (Yadav et al, 2021;Sapkal et al, 2021). Our study was conducted when B.1.617 lineages were dominating in India (INSACOG, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the unprecedented success in SARS-CoV-2 vaccine development, incorporating S protein from wild type Wuhan-Hu-1 strain, novel strains of SARS-CoV-2 have emerged facilitating mild to moderate escape from humoral immunity, which includes but not limited to B.1.1.7 (UK; alpha variant), B.1.351 (SA; beta variant), P.1 (Brazil; gamma variant), B.1.617.2 (India; delta variant) and recently Omicron (B.1.1.529) with its derivatives. Several studies reported a 2-to 4-fold reduction in neutralization against Delta, a 6-fold or higher reduction in neutralization against Beta, and a 29-fold reduction in neutralization against Omicron for both convalescent and vaccinated individuals 16,17,18 . Despite reduced vaccine efficacy against mutant strains, effectiveness remained high against hospitalization or severe disease 19 .…”
Section: Introductionmentioning
confidence: 99%